Tensile behaviour of S690 Q&T steel plate-to-plate joints - Yip, Jennie Chun Yee (2015)
There are many benefits that high strength steel (HSS) can offer in design and structures, which is why it has become such a topic of interest. However, there is still much to be done in the research of HSS and its usage for the designing of steel structures. Many factors have to be considered such that the steels still fall within the limitations in design codes. In particular, the tensile behaviour of plate-to-plate joints that are of HSS needs to be studied. Steel connections, particularly welded joints, are part of the assessment of the integrity the material can offer. An example of HSS is the Reheated Quenched & Tempered (RQT) 701 steel of Grade S690. The present study is to assess the suitability of RQT 701 steel in modern construction today, particularly in steel connections such as plate to plate joints. This paper will be going through its mechanical properties after Post Weld Heat Treatment (PWHT), through tensile coupon tests and a microscopy examination of its microstructure. It will then discuss the investigation of tensile behaviour of T-stub joints made of the Grade S690 steel by experimental study. The load-displacement relationship of the abovementioned T-stub joints will be predicted via an analytical approach. After doing a comparison of the experimental and analytical results, it is found that the analytical approach overestimates the load-carrying capacity of the studied joints. As the load carrying capacities were too close to the design values proposed by EC3, it is believed that current design methods may not be conservative enough for RQT-S690 because of the weakened Heat Affected Zone (HAZ) caused by welding.